2005
DOI: 10.1113/jphysiol.2005.094979
|View full text |Cite
|
Sign up to set email alerts
|

Economy of locomotion in high‐altitude Tibetan migrants exposed to normoxia

Abstract: High-altitude Tibetans undergo a pattern of adaptations to chronic hypoxia characterized, among others, by a more efficient aerobic performance compared with acclimatized lowlanders.To test whether such changes may persist upon descent to moderate altitude, oxygen uptake of 17 male Tibetan natives lifelong residents at 3500-4500 m was assessed within 1 month upon migration to 1300 m. Exercise protocols were: 5 min treadmill walking at 6 km h −1 on increasing inclines from +5 to +15% and 5 min running at 10 km … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 43 publications
1
24
2
Order By: Relevance
“…In any case, there are no reports of aerobic capacities getting near the values reported for elite endurance athletes (80 to 90 mL/kg Ϫ1 / min Ϫ1 ). But what seems to distinguish the Tibetans from other populations is that they are less penalized when working in hypoxia compared to normoxia by being able to reach a higher fraction of low-altitude aerobic capacity when exposed to hypoxia than lowlanders (Niu et al, 1995;Marconi et al, 2005). This characteristic is also present in Tibetans born at low altitude exposed for the first time to high altitude, a finding that supports the contention of an inborn quality for altitude adaptation in the Tibetans (Marconi et al, 2005).…”
Section: Maximal Oxygen Consumption and Exercise Capacitysupporting
confidence: 73%
“…In any case, there are no reports of aerobic capacities getting near the values reported for elite endurance athletes (80 to 90 mL/kg Ϫ1 / min Ϫ1 ). But what seems to distinguish the Tibetans from other populations is that they are less penalized when working in hypoxia compared to normoxia by being able to reach a higher fraction of low-altitude aerobic capacity when exposed to hypoxia than lowlanders (Niu et al, 1995;Marconi et al, 2005). This characteristic is also present in Tibetans born at low altitude exposed for the first time to high altitude, a finding that supports the contention of an inborn quality for altitude adaptation in the Tibetans (Marconi et al, 2005).…”
Section: Maximal Oxygen Consumption and Exercise Capacitysupporting
confidence: 73%
“…This is in contrast to recent work performed by Marconi and co-workers [ 42 ]. They reported that Tibet an migrants born and living between 3500 and 4500 m had a better treadmill assessed locomotor economy (assessed at 1300 m) as compared to Nepali born and living in the Kathmandu valley [ 42 ]. It was concluded that the increased economy in Tibetans was due to chronic hypoxia induced metabolic adaptations, although these still need to be elucidated.…”
Section: Leg Vo 2 Whole Body Vo 2 and Whole Body Work Effi Ciencycontrasting
confidence: 68%
“…Also when analyzing multiple data obtained from independent investigations no trend was observed toward higher work effi ciencies in high-altitude natives from around the world [ 7 ]. This is in contrast to recent work performed by Marconi and co-workers [ 42 ]. They reported that Tibet an migrants born and living between 3500 and 4500 m had a better treadmill assessed locomotor economy (assessed at 1300 m) as compared to Nepali born and living in the Kathmandu valley [ 42 ].…”
Section: Leg Vo 2 Whole Body Vo 2 and Whole Body Work Effi Ciencymentioning
confidence: 57%
“…Overall, these results do not support the original and previously untested suggestion of Sutton and colleagues (1988) that ''racing'' style toe clip pedals may reduce _ V O 2 by 8 -18% compared with cycling with flat pedals. Therefore, the significant reduction in _ V O 2 observed by Sutton and colleagues (1988) during their simulated ascent of Mount Everest is more likely to be a consequence of some other variable, such as an altitude-induced adaptation at the muscular level similar to that observed in native highlanders (Hochachka et al, 1991;Marconi, Marzorati, Sciuto, Ferri, & Cerretelli, 2005). Sutton and colleagues (1988) claimed that the addition of toe-clips and straps to flat pedals was the likely cause of a significant reduction (8 -18%) in submaximal _ V O 2 after 2 weeks spent at a simulated altitude of *4600 m. In the present study, however, the mean _ V O 2 was 2.1% higher for toe-clip pedals than flat pedals and there was a 99.9% probability that submaximal _ V O 2 was not at least 8% lower with toe-clip pedals.…”
Section: Discussionmentioning
confidence: 84%